IBON Philippines profile. - IBON Philippines Databank & Research Center (Manila IBON Philippines Databank & Research Center, 1996)
"The handbook consists of 16 volumes with an average of 150 page per volume. Each volume discusses a certain region of the country. The selected data emphasize the rich potential but sorry state of our natural resources. They present the backwardness of our productive means and the extreme inequality in the control of properties and income. It has also provided data on government statistics on poverty, unemployment and social services infrastructure. The profiles also cover data on natural resources, people's socio-economic status, production, and social and economic infrastructure. The data is presented through tables and graphs."
Region I Ilocos Region -- Region II Cagayan Valley -- Region III Central Luzon -- Region IV Southern Tagalog -- Region V Bicol Region --Region VI Western Visayas -- Region VII Central Visayas -- Region VIII Eastern Visayas -- Region IX Western Mindanao -- Region X Northern Mindanao -- Region XI Southern Mindanao -- Region XII Central Mindanao -- National Capital Region -- Autonomous Region of Muslim and Mindanao -- Cordillera Autonomous Region.
Published with the assistance of Diakomia.
Keywords: Philippines -- Economic conditions -- 1990-.; Philippines -- Social conditions -- 1990.; Philippines -- Statistics